2022
DOI: 10.7717/peerj.13481
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets and signaling pathways of active components of QiLing decoction against castration-resistant prostate cancer based on network pharmacology

Abstract: QiLing decoction (QLD) is a traditional Chinese medicine compound. This study aims to explore the therapeutic effect of QLD in castration-resistant prostate cancer (CRPC) and its potential bio-targets. A total of 51 active components and QLD 149 targets were identified using bioinformatics analysis. Additionally, five optimal hub target genes were screened including tumor protein P53 (TP53), interleukin-6 (IL-6), vascular endothelial growth factor-A (VEGF-A), caspase-3 (CASP-3), and estrogen receptor-1 (ESR-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…QLD is widely used for CRPC therapy in many clinical settings in China 16 , 15 . The combination of QLD with docetaxel improves the therapeutic effectiveness of docetaxel against CRPC by enhancing cancer cells' sensitivities to docetaxel cytotoxicity 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QLD is widely used for CRPC therapy in many clinical settings in China 16 , 15 . The combination of QLD with docetaxel improves the therapeutic effectiveness of docetaxel against CRPC by enhancing cancer cells' sensitivities to docetaxel cytotoxicity 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, our group reported that QLD suppressed docetaxel resistance and aerobic glycolysis in patients with CRPC, at least in part, by the regulation of long non-coding RNA SNHG10 14 . In 2022, their bio-informatic study further suggested a total of 51 active components and 149 potential bio-targets for QLD in the treatment of CRPC 15 . However, it is still unclear if QLD can also improve the sensitivity of the antiandrogen drug against prostate cancer cells and their underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In silico studies Prostate cancer related gene identi cation Target genes related to prostate cancer were identi ed by exploring the term prostate cancer in the GeneCards (https://www.genecards.org/) and DisGeNET (https://www.disgenet.org/) databases and different targets were downloaded into Excel format (Cao et al, 2022). The targets from two databases pooled and duplicates were removed to obtain the nal targets for the prostate cancer.…”
Section: Reagents and Chemicalsmentioning
confidence: 99%